Ring Formation and Hydration Effects in Electron Attachment to Misonidazole - Ončák, Milan; Meißner, Rebecca; Arthur-Baidoo, Eugene; Denifl, Stephan; Luxford, Thomas F M; Pysanenko, Andriy; Fárník, Michal; Pinkas, Jiří; Kočišek, Jaroslav (International journal of molecular sciences, 2019)
We study the reactivity of misonidazole with low-energy electrons in a water environment combining experiment and theoretical modelling. The environment is modelled by sequential hydration of misonidazole clusters in vacuum. The well-defined experimental conditions enable computational modeling of the observed reactions. While the NO 2 - dissociative electron attachment channel is suppressed, as also observed previously for other molecules, the OH - channel remains open. Such behavior is enabled by the high hydration energy of OH - and ring formation in the neutral radical co-fragment. These observations help to understand the mechanism of bio-reductive drug action. Electron-induced formation of covalent bonds is then important not only for biological processes but may find applications also in technology.
Keywords: Electrons; bond formation; misonidazol; elektrony; electron attachment; Solvents; spektrální analýza; rozpouštědla; molekulární struktura; voda; Spectrum Analysis; Molecular Structure; teoretické modely; Misonidazole; low-energy electron; molekulární modely; Models, Molecular; Models, Theoretical; misonidazole; clusters; Water